The Use of Polynomials to Represent Cost Functions - Beach, E. F. (Review of Economic Studies, 1949)
The Use of Polynomials to Represent Cost Functions Get access E. F. Beach E. F. Beach Montreal Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 16, Issue 3, 1949, Pages 158–169, https://doi.org/10.2307/2295917 Published: 01 January 1949